Molecular evolution and genetic diversity analysis of SFTS virus based on next-generation sequencing - Aqian Li; Lin Liu; Wei Wu; Yang Liu; Xiaoxia Huang; Chuan Li; Di Liu; Jiandong Li; Shiwen Wang; Dexin Li; Mifang Liang (Elsevier, 2021)
SFTS virus (SFTSV) is a novel bunyavirus, which was discovered as the etiological agent of severe fever with thrombocytopenia syndrome (SFTS) in China in 2009, and was now prevalent in at least 25 provinces in China. SFTS was subsequently identified in South Korea and Japan in 2012. To explore the molecular evolution and genetic characteristics of this newly identified pathogen, we reported 72 whole genome sequences of SFTSV, and built a dataset of SFTSV genome sequences containing 292 L-segment, 302 M-segment and 502 S-segment. We clearly divided SFTSV into six genotypes, Genotype A-F. It was found that genotype F was the dominant epidemic genotype of Japan, South Korea, and Zhejiang province of China. The coalescent analysis supported that SFTSV originated in the early 18th century from Zhejiang province, and Genotype F was the most primitive one. Henan, Hubei, and Anhui provinces which are located in Dabie Mountain area were mainly epidemic of Genotype A, which emerged relatively late but distributed widely. A total of 37 recombination events were identified, making SFTSV with a high recombination frequency (L segment 5.1%, M segment 3.6%, S segment 0.8%) among negative-strand segmented RNA viruses. It was identified that 19 reassortant strains belonged to 12 reassortment forms of SFTSV genome containing 6 newly identified forms. The reassortment virus and recombination in tick were both found for the first time. We also found many of genotype-specific mutation sites, 7 of which could be considered as potential molecular marker for genotype classification. This study promoted a more comprehensive understanding of the phylogeny and origin, and the genetic diversity of SFTSV, and it could help the studies of other newly discovered tick-borne bunyavirus as reference data and research ideas.